Przemiany kulturowe a rozwój społeczno-gospodarczy - Zając, Kazimierz; Kosiorowski, Daniel (Cultural Changes and Socio-Economic Development, 2005)
The objective of the paper is the verification of the hypothesis stating that there is relation between socio-economic and cultural development. In the empirical studies conducted for Polish territorial units the following multivariate statistical methods were applied: canonical correlation analysis, factor analysis and T2 Hotelling statistics. The main conclusion drawn from the studies is the one that cultural development is one of the national priorities since it leads to socio-economic development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 26-37